Alternative technology niches and sustainable development. Issue 4 (1st October 2016) - Smith, Adrian
Abstract : This paper contrasts two niche-based approaches to sustainable development, both recommended for greening technology systems. One is new, the other is old. In fact, a gap of thirty years separates Strategic Niche Management (SNM) from the Alternative Technology movement (AT), yet both share a niche-based perspective on change. Their core approach is to generate knowledge and disseminate lessons about sustainable technological practices through innovative, bottom-up activities. The ambition for both is to seed a sustainable transformation of incumbent technological regimes. SNM proves to be more managerial in its approach; while AT conceptualises niches as a much more grassroots activity. This reflects their different histories. Comparisons between the two uncover some fundamental issues regarding alternative technology niches and sustainable development.